Treating obesity using the combination of metformin and epigallocatechin-3-gallate - Zhican YANG; Xinyuan ZHAO; Ying LIU; Benchi ZHAO; Yi LUO; Jiansheng KANG; Qiaoping WANG (KeAi Communications Co., Ltd., 2022)
Objective: This study aimed to investigate the anti-obesity effects of the combination of metformin and epigallocatechin-3-gallate (EGCG) in a diet-induced obese (DIO) model. Methods: Male C57BL/6J mice were fed with high-fat diet (HFD, 60% fat) to establish a DIO model. The DIO mice were administered intragastrically daily with vehicle, metformin (Met, 250 mg/kg), EGCG (200 mg/kg), or mixture of Met and EGCG (Met/EGCG; 250 and 200 mg/kg) for 32 days. Body weight was measured daily at a fixed time point. An intraperitoneal glucose tolerance test was performed on day 26 after treatments. Body composition was determined by using nuclear magnetic resonance technology. Adipose tissues and major organs were collected after culling. Gene expression in brown adipose tissue (BAT) and subcutaneous white adipose tissue (scWAT) were detected by quantitative polymerase chain reaction. Results: Compared with the vehicle group, the body weight was significantly reduced in DIO mice in the Met and Met/EGCG groups. The weight loss rate in the Met and EGCG groups were 9.1% and 1.0%, respectively. However, Met/EGCG induced a 14.0% body weight loss, suggesting that the combination of Met and EGCG has a synergistic effect on reversing the body weight in DIO mice. Met/EGCG demonstrated beneficial effects on the subcutaneous fat, BAT, and glucose homeostasis in DIO mice. Furthermore, Met/EGCG did not significantly increase the thermogenic gene expression in BAT, whereas in scWAT, Met/EGCG showed moderate effects on the expression of specific markers of browning fat or beige fat. Conclusion: Metformin and EGCG have combined treatment effect on the body weight of DIO mice. Their combination might be a promising treatment approach for obesity.